Examining Sodium and Potassium Channel Conductances Involved in Hyperexcitability of Chemotherapy-Induced Peripheral Neuropathy: A Mathematical and Cell Culture-Based Study - Verma, Parul; Eaton, Muriel; Kienle, Achim; Flockerzi, Dietrich; Yang, Yang; Ramkrishna, Doraiswami (Frontiers in Computational Neuroscience, 2020)
Chemotherapy-induced peripheral neuropathy (CIPN) is a prevalent, painful side effect which arises due to a number of chemotherapy agents. CIPN can have a prolonged effect on quality of life. Chemotherapy treatment is often reduced or stopped altogether because of the severe pain. Currently, there are no FDA-approved treatments for CIPN partially due to its complex pathogenesis in multiple pathways involving a variety of channels, speciﬁcally, voltage-gated ion channels. One aspect of neuropathic pain in vitro is hyperexcitability in dorsal root ganglia (DRG) peripheral sensory neurons. Our study employs bifurcation theory to investigate the role of voltage-gated ion channels in inducing hyperexcitability as a consequence of spontaneous ﬁring due to the common chemotherapy agent paclitaxel. Our mathematical investigation of a reductionist DRG neuron model comprised of sodium channel Nav1.7, sodium channel Nav1.8, delayed rectiﬁer potassium channel, A-type transient potassium channel, and a leak channel suggests that Nav1.8 and delayed rectiﬁer potassium channel conductances are critical for hyperexcitability of small DRG neurons. Introducing paclitaxel into the model, our bifurcation analysis predicts that hyperexcitability is highest for a medium dose of paclitaxel, which is supported by multi-electrode array(MEA) recordings. Furthermore, our ﬁndings using MEA reveal that Nav1.8 blocker A-803467 and delayed rectiﬁer potassium enhancer L-alpha-phosphatidyl-D.myo-inositol 4,5-diphosphate, dioctanoyl (PIP2) can reduce paclitaxel-induced hyperexcitability of DRG neurons. Our approach can be readily extended and used to investigate various other contributors of hyperexcitability in CIPN.